Samal Island and its people narratives of power in the landscapes of a New City - Mangahas, Maria F. (Banwa, 2004)
In the frontier zone of Southeastern Mindanao, the general sociological observation that social reality stands “in immediate relation to the distribution of power” proves to be a much more complex and dynamic state of being. This paper outlines several recurrent conversations about a particular island location in Southern Philippines. The sizeable island of Samal in the Davao Gulf is at its closest point only 15 minutes away from Davao City. It became the “Island Garden City of Samal” in 1998, but before that surprisingly few people in Davao City were even aware that there was an island called “Samal” nearby. Traveling around the island and conducting fieldwork in 1996-1997 I encountered many kinds of people and several recurrent conversations about Samal as a place. These local discourses tell of interregional migration and movement, and reflect active local engagement with the processes of “Bisayanization” and integration within the national mainstream, globalization, capitalism, and modernization in the Davao region. The paper situates each of the different kinds of claims on the landscape within the existing ethnographic, demographic, and historical picture for the region, and ends up describing a setting that is actually many different kinds of reality at the same time. Six narratives of the landscape are discussed: Samal Island as valuable real estate; as mystic place of “giants” and “ancestral domain”; as out-of-the-way and risky, where a visitor should watch out for ‘poisoning”; as recently settled frontier; as a promised and prophesied land; and, finally, as a landscape also inhabited by unseen beings that are “not like us,” widely feared to be exacting taxes in human life as large scale government and multinational-led infrastructural development proceeded in 1997. The paper examines each of these in turn, as they describe and address larger issues of identity, land, and power.